The Effect of Liquid Organic Fertilizer and Cow Manure on the Growth and Yield of Red Onion Plants (Allium ascalonicum L.) - kusuma, galih sekar permata; Haryuni; Suprapti, Endang; Wiyono (Journal of Rural and Urban Community Studies, 2025)
Abstract Shallots (Allium ascalonicum L.) is a horticultural plant which is widely used as a kitchen spice and as an ingredient in traditional medicine. This research aims to determine the effect of liquid organic fertilizer doses and cow manure doses on the growth and yield of shallots. The research used a Complete Randomized Block Design (RAKL) with two factors, namely the dose of liquid organic fertilizer (0 ml, 10 ml, 20 ml per plant) and the dose of cow manure (0, 5, 10, 15 tons/ha), with three replications so that there were 12 treatment combinations. The results of the research showed that applying liquid organic fertilizer had an effect on plant height and fresh stover weight, but had no effect on dry stover weight. Liquid organic fertilizer also affects the number of tubers and tuber weight per plant, but has no effect on tuber diameter. Cow manure affects plant height, number of leaves, weight of fresh stover, as well as crop yields such as number of tubers, tuber weight and tuber diameter. The combination of liquid organic fertilizer and cow manure had an effect on the number of leaves and weight of fresh stover, but had no effect on plant height, dry stover weight and tuber yield. The best combination was obtained in the treatment of 20 ml liquid organic fertilizer and 15 tons/ha of cow manure (G2S3).